Mendidik Generasi Millenial Di Era Globalisasi - Catur Lestari Wijayanti (Program Studi Pendidikan Islam Anak Usia Dini, 2021)
Abstract:. The process of linkage and dependence between individuals, group, between nations and countries aroun the world through media that is increasingly widespread, easy, and affordable for the public to accept various new information and communication techologies that come from all corners of the world so as to build public opinion that seeks to see the condition of generations millennials who lives in the era of globalization, both in positive and negative conditions.